Financial Soundness of Indian Life Insurance Firms : An Investigation Based on the CARAMELS Framework - Chakraborty, Joy (Indian Journal of Finance, 2017)
Liberalization of the Indian life insurance sector has brought about a lot of opportunities and challenges. The enactment of the IRDAI Act in 1999 brought in a lot of opportunities with the rising presence of private and foreign players in the country's life insurance sector. On the flip side, the Indian life insurance sector experienced severe setbacks in terms of low profits and negative investment yield post 2007-08 owing to the contagion effects of the global financial crisis that erupted in U.S. during the year 2007-08. At the same time, the liberalization of the country's life insurance sector has further raised concerns for the life insurers in ensuring financial soundness for timely payment of assured returns to the policyholders' besides protection of the policyholders' interests. The present study provided an assessment of the financial soundness of 18 life insurance firms in India during the post-deregulation study-period from 2008-09 to 2014-15 in the backdrop of the U.S. financial crisis. In this regard, the ratio-based CARAMELS framework was used in line with the financial soundness indicators (FSIs), as proposed by the researchers of the World Bank and International Monetary Fund (IMF). The present study pointed out the impressive performances of the private life insurers in overpowering the dominance of the state-owned LICI, besides highlighting the contagion effects of the global financial crisis on the country's life insurance sector.